2005
DOI: 10.1177/0887302x0502300403
|View full text |Cite
|
Sign up to set email alerts
|

Border Crossing: Active and Deep Learning in a Large Global Consumption Class

Abstract: This article describes how a class on global consumers was transformed into an interactive class using both active and deep learning techniques. Good teachers understand that to achieve a level of lasting learning, students must be engaged on many levels. While much has been written about active learning, the concept of deep learning is limited, particularly when applied to a large class setting. This paper describes active and deep teaching strategies and provides learning exercises for their integration into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Indeed, in a metrics-driven UK HE context, graduate employability is a key indicator of course and university success. To raise levels of graduate employability, several commentators have devised lists of requisite skills to be developed, including team working, problem solving and communication (Hawley 2005;CBI 2009;Power 2010;CIPD 2016), all of which benefit from working across discipline boundaries. Marcketti and Karpova's (2014) study highlighted the value of working collaboratively with industry from the students' perspective, concluding that students appreciated the opportunity of co-working to develop problem solving skills in a real world environment with their peers.…”
Section: Interdisciplinarity: Tandlmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in a metrics-driven UK HE context, graduate employability is a key indicator of course and university success. To raise levels of graduate employability, several commentators have devised lists of requisite skills to be developed, including team working, problem solving and communication (Hawley 2005;CBI 2009;Power 2010;CIPD 2016), all of which benefit from working across discipline boundaries. Marcketti and Karpova's (2014) study highlighted the value of working collaboratively with industry from the students' perspective, concluding that students appreciated the opportunity of co-working to develop problem solving skills in a real world environment with their peers.…”
Section: Interdisciplinarity: Tandlmentioning
confidence: 99%
“…More recently, it was stated that new reforms in HE will focus on technical skills and routes into key occupations (BIS 2016). Furthermore, there is a plethora of literature to support collaboration, use of live briefs and the value of problem solving in relation to the HE employability agenda across a broad range of disciplines (Stember 1991;Hawley 2005;CBI 2009;Power 2010;Marcketti and Karpova 2014;CIPD 2016;De Hei et al 2016). The espoused values of several professional bodies and councils reinforce the superiority of multidisciplinary teams for solving complex challenges (for example, The Royal Academy of Engineering (RAE, 2012) and The Design Council (DC 2015).…”
Section: Literature Review: Barriers To and Facilitators Of Interdiscmentioning
confidence: 99%
“…Eich (2008) commented Ingram, 2004). In general, experiential learning which engages students at the emotional, physical, and cognitive levels helps students make connections between their learning and their personal lives; forming deeper, longer-lasting learning (Hawley, 2005;Kolb, 1984). An overriding theme in developing student leadership behaviors and skill is the aspect of doing leadership.…”
mentioning
confidence: 99%
“…Previous work (Power, 2010b;) identified that four key statements are required to enhance graduate employability in the apparel sector: the development of technical competencies (knowledge, understanding and competency), the expansion of life skills for a globalised knowledge economy (key, occupational and professional skills), the advancement of high order cognitive skills (analysis, synthesis and evaluation), and the appreciation of metacognitive strategies (learning how to learn, appreciating skill development). Many authors have acknowledged that it is not enough for the new breed of graduates to have passed assessments as they must have developed skills of problem solving, teamwork and most importantly passion for their selected career (Hawley, 2005;Kimmons & Spruiell, 2005;Fiore et al, 2005). The challenge is balancing all of the above factors in large cohorts and maintaining a high level of student satisfaction during the course of study.…”
Section: Flexible Learningmentioning
confidence: 99%